Biochar decreased N loss from paddy ecosystem under alternate wetting and drying in the Lower Liaohe River Plain, China - Feng Zhang; Taotao Chen; Hongyuan Zhu; Zhe Wang; Wanting Zhang; Wanning Dai; Daocai Chi; Guimin Xia (Agricultural Water Management, 2024)
Biochar addition to soil is widely utilized to enhance carbon sequestration and reduce fertilizer N losses. However, little research has been studied on the effect of biochar on reactive gaseous N losses, N leaching and grain yield in paddy ecosystems under water stress, especially in the Lower Liaohe River Plain with a higher water percolation. Our experiment was carried out in 2020 and 2021 utilizing a split-plot design with continuously flooding irrigation and alternate wetting and drying irrigation as main plots and without biochar addition and with 20 t·ha−1 rice husk-derived biochar addition as sub-plots. The results showed that alternate wetting and drying irrigation respectively, decreased N leaching and reactive N losses by 15.9 % and 11.3 % but also respectively, increased seasonal cumulative NH3 volatilization and N2O emissions by 5.0 % and 210 % on average. Rice husk-derived biochar addition significantly mitigated seasonal cumulative NH3 volatilization and N2O emissions by 8.8 % and 19.7 % in 2020, 20.7 % and 19.2 % in 2021, respectively, and decreased inorganic N leaching and reactive N losses by 8.3 % and 14.1 % in 2021. Biochar addition coupling with alternate wetting and drying respectively, mitigated cumulative NH3 volatilization and N2O emissions by 7.3 % and 19.3 % in 2020, and, 22.7 % and 22.0 % in 2021 as compared to that without biochar. Biochar did not differ from without biochar in inorganic N leaching under alternate wetting and drying irrigation in both years but significantly reduced reactive N losses by 17.8 % in 2021, which efficiently inhibited the alternate wetting and drying induced negative effects on the increase in reactive N losses. Therefore, biochar addition to paddy ecosystems under alternate wetting and drying could realize sustainable utilization of water resources, increase soil N fixation, and mitigate N losses.